Recovery of Vanillin and Syringaldehyde from Lignin Oxidation: A Review of Separation and Purification Processes. Issue 3 (2nd July 2016) - Mota, Maria Inês F.; Rodrigues Pinto, Paula C.; Loureiro, José Miguel; Rodrigues, Alírio E.
Abstract : Lignin is an underexploited side-stream of pulp and paper industry and biorefineries, being used for energy production at mill site or as low value material for dispersants or binding applications. However, an integrated process of reaction and separation can be implemented for the production of high added-value monomeric phenolic chemicals such as vanillin and syringaldehyde. In this review, the main research advances in the recovery of vanillin and syringaldehyde resulting from oxidation of lignin are addressed, covering various separation methodologies namely liquid-liquid extraction, supercritical fluid extraction, distillation, crystallization, membrane separation, and adsorption. Studies in this area started in the early years of the 20 th century, but in the last decades several processes have been suggested, mainly for vanillin separation. Finding the ultimate industrially feasible process is still a necessary task and this review points out the most promising technologies and sequence of processes.